Allogeneic haematopoietic stem cell transplantation: results of the procedure in The Lower Silesian Center of Cellular Transplantation with National Bone Marrow Donors Registry - Lange, Andrzej; Sędzimirska, Mariola (Contemporary Oncology/Współczesna Onkologia, 2006)
HSCT from an allogeneic donor is a life-saving procedure in some inborn errors and blood cancers. Analysis of survival curves of 353 patients, among them 280 with leukaemia and lymphomas, shows: (1) in general 50% of patients with blood cancers enjoy 5-year survival, (2) a plateau is reached after 5 years, (3) stage of disease at transplantation affects outcome, (4) survival of pts receiving transplant from unrelated or haploidentical donors is fairly inferior as compared to sibling transplantation and (5) survival rate of pts receiving transplant in last 10 years is superior to that in pts transplanted in years 1889-1996.